Transportation system functions during hurricane Response: A systematic review of modes and methods. (March 2023) - Islam, Riffat; Jones, Steven; Hudnall, Matthew
Highlights: This study analyzed transportation system functions during hurricane response. The systematic review of literature focused on modes used and methods adopted. The most common research methods were found to be optimization and simulation. In evacuation plans, automobiles were found to predominate over public transit. Readers will be able to choose studies by common categories using 3 web-based tools. Abstract: The transportation sector is critical to the emergency response during a hurricane. This research does a systematic assessment of the literature to determine how the transportation system actively engages in the aftermath of a hurricane by examining the transportation system's major function indicators- "Evacuation Routing", "Emergency Services", and "Search & Rescue". To accomplish this goal, 86 academic publications were examined using the Web of Science and Scopus databases. The emergency response functions of the transportation system were evaluated using academic research methods, with various modes of transport considered. In the studies, optimization and simulation techniques were found to be common research methodologies, whereas personal cars and public transportation were used more often than other modes of transportation. The findings of the study may provide useful guidelines to researchers in the area, as well as serve as a research reference for future studies on hurricane emergency transportation system response.